2008
DOI: 10.1002/ptr.2720
|View full text |Cite
|
Sign up to set email alerts
|

Yeast hydrolysate induces longitudinal bone growth and growth hormone release in rats

Abstract: This study investigated the growth promoting effects of yeast extract (YH) fed to Sprague-Dawley male rats (3 weeks old) for 4 weeks. The negative (N)-control and positive (P)-control groups were given a daily oral administration of saline and foremilk (1 g/kg of BW), respectively, and the YH-1 and YH-2 groups were given daily administrations of YH (0.5 and 1 g/kg of BW, respectively). After 4 weeks, the YH-1, YH-2 and P-control groups showed significant differences in the body weight gain compared with the N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…The synthesis and secretion of GH in somatotroph cells of the anterior pituitary gland may be induced by several natural products (17,18). For instance, administration of yeast extract for four weeks was shown to increase the body weight and GH secretion of young SD male rats (19). The bioassay-guided fraction of MeOH extract from the fenugreek (Trigonella foenum-graecum L.) seed stimulates the release of GH from rat pituitary cells.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis and secretion of GH in somatotroph cells of the anterior pituitary gland may be induced by several natural products (17,18). For instance, administration of yeast extract for four weeks was shown to increase the body weight and GH secretion of young SD male rats (19). The bioassay-guided fraction of MeOH extract from the fenugreek (Trigonella foenum-graecum L.) seed stimulates the release of GH from rat pituitary cells.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al (2009) and Lee et al (2011) reported that yeast hydrolysate increased the proximal epiphyseal length of bone, accelerated its longitudinal extension and stimulated growth hormone secretion in young rats. There is no study of the effect of the yeast on the epiphyseal growth plate of broiler chickens.…”
Section: Epiphyseal Growth Platesmentioning
confidence: 99%
“…Leg abnormalities cause pain and discomfort for broilers Mcgeown et al, 1999), and severe lameness limits the broilers' access to feeders and water Knowles et al, 2008). Consequently, chickens can be exposed to hunger, thirst, and dehydration (Butterworth et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…6,7) Recently, yeast hydrolysate has revealed various physiological effect of according to molecular weight. In Kim et al study, 8) yeast hydrolysate with 10-30 kDa molecular weight increased longitudinal bone growth and growth hormone secretion in adolescent Sprague-Dawley (SD) rats. And yeast hydrolysate with below 10 kDa molecular weight has displayed the anti-obesity effects in SD rats fed a high fat diet and obese women.…”
Section: Introductionmentioning
confidence: 99%